NK cell receptor profiling of endometrial and decidual NK cells reveals pregnancy-induced adaptations - Feyaerts, Dorien; Benner, Marilen; Comitini, Gaia; Shadmanfar, Wijs; van der Heijden, Olivier W.H.; Joosten, Irma; van der Molen, Renate G. (Frontiers in Immunology, 2024)
Natural killer (NK) cells, with a unique NK cell receptor phenotype, are abundantly present in the nonpregnant (endometrium) and pregnant (decidua) human uterine mucosa. It is hypothesized that NK cells in the endometrium are precursors for decidual NK cells present during pregnancy. Microenvironmental changes can alter the phenotype of NK cells, but it is unclear whether decidual NK cell precursors in the endometrium alter their NK cell receptor repertoire under the influence of pregnancy. To examine whether decidual NK cell precursors reveal phenotypic modifications upon pregnancy, we immunophenotyped the NK cell receptor repertoire of both endometrial and early-pregnancy decidual NK cells. We showed that NK cells in pre-pregnancy endometrium have a different phenotypic composition compared to NK cells in early-pregnancy decidua. The frequency of killer-immunoglobulin-like receptor (KIR) expressing NK cells, especially KIR2DS1, KIR2DL2L3S2, and KIR2DL2S2 was significantly lower in decidua, while the frequency of NK cells expressing activating receptors NKG2D, NKp30, NKp46, and CD244 was significantly higher compared to endometrium.Furthermore, co-expression patterns showed a lower frequency of NK cells co-expressing KIR3DL1S1 and KIR2DL2L3S2 in decidua. Our results provide new insights into the adaptations in NK cell receptor repertoire composition that NK cells in the uterine mucosa undergo upon pregnancy.